Pore Size Distribution and Microstructure of Oil Palm Shell Heat Treated at 300 C Followed by Slow or Fast Heating Treatment - Joko Sulistyo; Toshimitsu Hata; Yuji Imamura; Purnomo Darmaji; Sri Nugroho Marsoem (Masyarakat Peneliti Kayu Indonesia, 2018)
Pore size distribution and microstructure development of oil palm shell heat treated at 300ºC and treated at 300ºC and recarbonization at 600ºC followed by slow- or fast heating treatment up to 700ºC were investigated by small angle X-ray scattering (SAXS), N2 gas adsorption and Raman spectroscopy. On oil palm shell heat-treated at 300ºC, slow heating treatment gave the widening micropore along with the ordering microstructure; but fast heating treatment produced charcoal with a narrow diameter of micropore with wider pore size distribution and the disordering microstructure. On oil palm shell heat treated at 300ºC and recarbonization at 600ºC, slow heating treatment contributed on the opening new micropore with ordering microstructure, but some parts of micropore showing inaccessible for N2 gas. Meanwhile, fast heating treatment with the heating rate from 75 to 250ºC/min increased BET surface area with similar pore size distribution and the disordering microstructure.